Seasonal cycles of secondary organic aerosol tracers in rural Guangzhou, Southern China: The importance of atmospheric oxidants. (September 2018) - Yuan, Qi; Lai, Senchao; Song, Junwei; Ding, Xiang; Zheng, Lishan; Wang, Xinming; Zhao, Yan; Zheng, Junyu; Yue, Dingli; Zhong, Liuju; Niu, Xiaojun; Zhang, Yingyi
Abstract: Thirteen secondary organic aerosol (SOA) tracers of isoprene (SOAI ), monoterpenes (SOAM ), sesquiterpenes (SOAS ) and aromatics (SOAA ) in fine particulate matter (PM2.5 ) were measured at a Pearl River Delta (PRD) regional site for one year. The characteristics including their seasonal cycles and the factors influencing their formation in this region were studied. The seasonal patterns of SOAI, SOAM and SOAS tracers were characterized over three enhancement periods in summer (I), autumn (II) and winter (III), while the elevations of SOAA tracer (i.e., 2, 3-dihydroxy-4-oxopentanoic acid, DHOPA) were observed in Periods II and III. We found that SOA formed from different biogenic precursors could be driven by several factors during a one-year seasonal cycle. Isoprene emission controlled SOAI formation throughout the year, while monoterpene and sesquiterpene emissions facilitated SOAM and SOAS formation in summer rather than in other seasons. The influence of atmospheric oxidants (O x ) was found to be an important factor of the formation of SOAM tracers during the enhancement periods in autumn and winter. The formation of SOAS tracer was influenced by the precursor emissions in summer, atmospheric oxidation in autumn and probably also by biomass burning in both summer and winter. In this study, we could not see the strong contribution of biomass burning to DHOPA as suggested by previous studies in this region. Instead, good correlations between observed DHOPA and O x as well as [NO2 ][O3 ] suggest the involvement of both ozone (O3 ) and nitrogen dioxide (NO2 ) in the formation of DHOPA. The results showed that regional air pollution may not only increase the emissions of aromatic precursors but also can greatly promote the formation processes. Graphical abstract: Image 1 Highlights: Thirteen SOA tracers were investigated at a regional site in rural Guangzhou. SOA tracers from individual precursors exhibited unique seasonal variations. Terpene SOA formation was enhanced by O x especially in autumn. DHOPA formation involves O3 and NO x . Abstract : Atmospheric oxidants associated with anthropogenic air pollution in fast developing regions are important to enhance SOA formation.